Agricultural diversity linkage to income, wealth, diets and nutrition: Case of Lilongwe district in Malawi - Fatch, Paul; Masangano, Charles; Jordan, Irmgard; Hilger, Thomas; Kalimbira, Alexander; Glas, Maria Gracia; Roehlig, Anna; Chiutsi-Phiri, Gabriella; Mangani Kamoto, Judith Francesca; Mambo, Isaac; Nuppenau, Ernst-August (Elsevier, 2023)
There is global debate whether to diversify agricultural production. A study was conducted in 2016 and 2017 in Lilongwe district, Malawi, to determine effects of agricultural diversity on income, wealth, diets and nutrition. A cross-sectional design was used in surveys on agriculture, income, assets, and nutrition coupled with anthropometric measurements targeting children, men, and women in 424 households. Using an agricultural diversity index constituting crop livestock and fruit diversity, level of agricultural diversity was 28.22%). Bivariate correlation analysis showed that agricultural diversity had a significant positive relationship with household income (r = 0.369), wealth (r = 0.363), and dietary diversity (r = 0.144 for children, r = 0.298 for women, and r = 0.211 for men). However, agricultural diversity had no significant effect on nutritional status of children, women, and men. This implies that to influence nutrition, other factors, such as better health, need to complement agricultural diversity.